2001
DOI: 10.1046/j.1528-1157.2001.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Status Epilepticus in Adults in Germany: A Prospective, Population‐Based Study

Abstract: Summary:Purpose: To determine the incidence and casefatality rate of status epilepticus (SE) in adults in Hessen, Germany, we performed a prospective, population-based study from July 1997 through June 1999.Methods: All adult patients residing within the zip-code area 35 (area-35) with SE were included. Area-35 had 743.285 adult inhabitants, including 123.353 adult inhabitants of the primary service area of the University Hospital Marburg (PS-area). Patients were reported by 16 hospitals in the area and were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
374
14
25

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 473 publications
(469 citation statements)
references
References 11 publications
48
374
14
25
Order By: Relevance
“…SE was associated with short-term mortality rates of ∼20% (Hauser, 1990;DeLorenzo et al, 1995;Logroscino et al, 1997;Lowenstein and Alldredge, 1998;Knake et al, 2001;Rosenow et al, 2002;Wu et al, 2002). Patient age at diagnosis, etiology of SE (especially anoxia), severity of the underlying disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SE was associated with short-term mortality rates of ∼20% (Hauser, 1990;DeLorenzo et al, 1995;Logroscino et al, 1997;Lowenstein and Alldredge, 1998;Knake et al, 2001;Rosenow et al, 2002;Wu et al, 2002). Patient age at diagnosis, etiology of SE (especially anoxia), severity of the underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…The SE group consisted of patients from the zip-code area 35-, Hessen, Germany, with 743,258 adult inhabitants (July 1, 1998), who were prospectively screened for an epidemiologic study performed by the Department of Neurology at the University Hospitals in Marburg, Germany (Knake et al, 2001). Included in this study were all patients aged 18 years or older and diagnosed with SE between July 1997 and March 2000.…”
Section: Status Epilepticus Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…However, subsequent European studies have shown that CPSE amounts to 16 43% of all SE cases [Vignatelli et al 2003;Knake et al 2001;Coeytaux et al 2000].…”
Section: Cpsementioning
confidence: 99%